2010
DOI: 10.2147/nss.s6934
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive performance and behavior before and after treatment for sleep-disordered breathing in children

Abstract: Neurocognitive and behavioral problems are increasingly reported in children with sleep-disordered breathing (SDB). The impact of treatment for SDB on neurocognition and behavior is, therefore, an issue of increasing importance. To date, there has been little consideration given to the quality of studies when reviewing associated neurocognitive and behavioral problems in children with SDB, and furthermore, there has been little systematic review of treatment outcomes. The aim of this review was to provide an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 173 publications
2
31
0
1
Order By: Relevance
“…However, there was a significant improvement in executive functioning, attention, behaviour and excessive daytime sleepiness as rated by parents, which was predicted by the preoperative severity of symptoms but not by the AHI (class I) [113,177]. Similarly, two systematic reviews of mostly class III and IV studies concluded that adenotonsillectomy is followed by improvements in behavioural problems and neurocognitive skills irrespective of SDB severity [178,179].…”
Section: 4mentioning
confidence: 96%
See 1 more Smart Citation
“…However, there was a significant improvement in executive functioning, attention, behaviour and excessive daytime sleepiness as rated by parents, which was predicted by the preoperative severity of symptoms but not by the AHI (class I) [113,177]. Similarly, two systematic reviews of mostly class III and IV studies concluded that adenotonsillectomy is followed by improvements in behavioural problems and neurocognitive skills irrespective of SDB severity [178,179].…”
Section: 4mentioning
confidence: 96%
“…In the CHAT study, changes in the attention and executive function objective scores from baseline to follow-up did not differ between the early-adenotonsillectomy and the watchful-waiting groups but there were significant gains in executive functioning, attention, behaviour and daytime sleepiness as rated by parents (class I) [126,177]. Both the CHAT study and older low quality evidence have demonstrated that the favourable changes in sleepiness, behavioural problems, attention-deficit, hyperactivity symptoms, neurocognitive skills, quality of life scores and symptoms of SDB following adenotonsillectomy are not related to the preoperative severity of obstructive SDB (systematic reviews and class I-II) [113,[176][177][178][179]221]. In contrast, the increase in BMI z-score is positively related to the preoperative AHI (class I) [180].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a comprehensive review, Kohler et al found that less than half of 22 studies reported an increased prevalence of behavioral problems in children with OSAS. 13 For example, O'Brien found no difference in behavior, assessed with the CBCL, between 35 children with OSAS compared to controls. 14 Similarly, although many studies have shown improvements in behavior after adenotonsillectomy, 13 others have not.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies report significant differences between snoring and non-snoring children in intelligence, attention, and executive functions. 15,17,19,[21][22][23] Less commonly reported deficits are in memory, visual-spatial ability, language skills, and sensomotor functions. 9,17 Despite these differences, it is notable that the mean Intelligence Quotient (IQ) and subtest scores for snoring children have usually been within the standardized normal range.…”
Section: Introductionmentioning
confidence: 99%
“…9,17 Despite these differences, it is notable that the mean Intelligence Quotient (IQ) and subtest scores for snoring children have usually been within the standardized normal range. 22 Poor academic performance has been found in snoring children, 8 as well as higher risk for academic underachievement even after snoring has resolved. 24 In a longitudinal study, children with a history of SDB in the first 5 years of life had increased likelihood of having special educational needs at the age of 8.…”
Section: Introductionmentioning
confidence: 99%